Efficacy of observational hand hygiene audit with targeted feedback on doctors' hand hygiene compliance: A retrospective time series analysis. Issue 4 (July 2019) - Smiddy, Maura P; Murphy, Olive M; Savage, Eileen; Fitzgerald, Anthony P; O' Sullivan, Brenda; Murphy, Catriona; Bernard, Margaret; Browne, John P
Background: Healthcare-associated infection compromises patient safety. Compliance with hand hygiene (HH) guidelines has been shown to be an effective method of reducing infection; however, it remains suboptimal and poorer among doctors compared to other healthcare workers. The aim of this study is to determine the relationship between an individualised observational hand hygiene audit (OHHA) and feedback intervention with observed HH compliance. Methods: We used a retrospective interrupted time series design using OHHA data from a five-year period, 2011–2015. OHHA indicated poorer HH compliance among doctors than other healthcare workers in a 345-bed acute private hospital. An increase in orthopaedic surgical site infection prompted additional auditing of the orthopaedic unit further identifying substandard HH compliance among orthopaedic surgeons. In addition to ongoing HH interventions, an individualised hand hygiene audit and feedback intervention focusing on consultant orthopaedic surgeons was implemented. Observed HH compliance improved. The intervention was then extended to include all consultant doctors at the study site. Audit was implemented by trained clinical nurse managers during clinical rounds. Written audit feedback was provided by the infection prevention and control team. Results: HH compliance increased significantly among both orthopaedic surgeons and other consultant doctors, P < 0.05. Conclusion: An individualised audit and feedback intervention was effective in improving compliance. Incorporation of OHHA with individualised feedback into routine daily practice needs to be considered as a quality improvement opportunity. This study has the potential to inform other audit and feedback interventions to maximise effectiveness and ensure implementation.